A review on characteristics of composite and advanced materials used for aerospace applications. (2022) - Tiwary, Akash; Kumar, Raman; Chohan, Jasgurpreet Singh
Abstract: Space is a stupendous and elephantine field that needs immense exploration and the advancements in the field of spacecraft materials are the top-notch field of today's research. The objective of the article is to examine the compositions of advance and composite materials used in the designing of space shuttle. The present work will discuss the applications and mechanical properties of reinforced materials used in the aerospace industry. Moreover, the paper is focused to highlight the usage and endurance limits of aluminum alloys in the air frame structure. An attempt has been made to provide the distribution of metallic materials in the structure of space shuttle through graphical representation. The thermodynamic characteristics of composite materials and possible advancements in the composite materials are discussed. The merits and demerits of composites such as advance carbon, reinforced carbon, flexible insulation blanket etc. in air shuttle fabrication are discussed to provide further directions for researchers. The developmental stages and growth of space materials are provided to select the suitable compositions of space shuttle materials.